Inoculation with spores of Pisolithus microcarpus and amendment with rock phosphate in seedlings of Eucalyptus grandis - Abreu, Vanessa Pereira de (2012)
The objective of this study was to evaluate the use of spores of Pisolithus microcarpus and rock phosphate (RP) in low-cost inoculation programs of Eucalyptus grandis in nurseries. Although the treatments did not increase plant growth, there was significant difference in dry mass of the root system and partition of carbon in the plant. Inoculation promoted a significant increase in the mycorrhization rates, but the doses of RN used in this study did not affect the establishment of the association. Additional studies are being conducted to optimize the procedure and inoculated with spores.